Assessment of the monuments of history list by students of university of economics - Laskowski, Andrzej (Protection of Cultural Heritage, 2019)
The article presents the results of the task given to students of Commodity Studies at the Cracow University of Economics in the spring of 2018 within the framework of the subject Protection of Cultural Property with Customs Aspects. The students’ task was to critically address the content of the list by indicating those places and objects which they found surprising or objectionable on the list and proposing those which in their opinion should be included but are not. In this first category, most people (as many as 8 out of 32 who spoke) were surprised at the inclusion of a stud farm in Janów Podlaski on the list, 5 of which decided that the farm should not be on the list at all. Łódź - a multicultural landscape of an industrial city - was also assessed very critically (3 votes of strong disapproval). As for adding new items to the list, most people (5) noticed the need to include Auschwitz Birkenau, the German Nazi concentration and extermination camp, and the Przemyśl Fortress (4), which has since actually happened in the latter case. The implementation of the task showed that such a form of protection of historical monuments is necessary in Poland, and the emotions aroused by the content of the MH list may have an educational and popularizing value.